Intelligent Wireless Remote Control System Design for a Biped Robot - Lin, Chih-Min; Chen, Chih-Hsuan (Proceedings of Engineering and Technology Innovation, 2017)
This paper presents the design and implementation of an intelligent wireless remote control system for a biped robot. A recurrent cerebellar model neural network (RCMNN) is introduced, then it is used for the walking control of a biped robot. Furthermore, the remote communication module is designed for the remote control of a robot. Finally, experimental results show that the developed system can achieve satisfactory control performance for the walking control of a high-order nonlinear biped robot.